Coordination between intra- and extracellular forces regulates focal adhesion dynamics - Sarangi, Bibhu Ranjan; Gupta, Mukund; Doss, Bryant L.; Tissot, Nicolas; Lam, France; Mège, René Marc; Borghi, Nicolas; Ladoux, Benoit (Nano Letters, 2017)
Focal adhesions (FAs) are important mediators of cell-substrate interactions. One of their key functions is the transmission of forces between the intracellular acto-myosin network and the substrate. However, the relationships between cell traction forces, FA architecture, and molecular forces within FAs are poorly understood. Here, by combining Förster resonance energy transfer (FRET)-based molecular force biosensors with micropillar-based traction force sensors and high-resolution fluorescence microscopy, we simultaneously map molecular tension across vinculin, a key protein in FAs, and traction forces at FAs. Our results reveal strong spatiotemporal correlations between vinculin tension and cell traction forces at FAs throughout a wide range of substrate stiffnesses. Furthermore, we find that molecular tension within individual FAs follows a biphasic distribution from the proximal (toward the cell nucleus) to distal end (toward the cell edge). Using super-resolution imaging, we show that such a distribution relates to that of FA proteins. On the basis of our experimental data, we propose a model in which FA dynamics results from tension changes along the FAs.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Cell traction force; Focal adhesion; Mechanobiology; Micropillar substrate; Molecular force sensor; Rigidity sensing; Vinculin